2021
DOI: 10.3390/ma14071806
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mechanisms of GFRP Scarf Joints under Tensile Load

Abstract: A potential repair alternative to restoring the mechanical properties of lightweight fiber-reinforced polymer (FRP) structures is to locally patch these areas with scarf joints. The effects of such repair methods on the structural integrity, however, are still largely unknown. In this paper, the mechanical property restoration, failure mechanism, and influence of fiber orientation mismatch between parent and repair materials of 1:50 scarf joints are studied on monolithic glass fiber-reinforced polymer (GFRP) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The patch was fabricated by placing the largest ply as a first taper layup sequence according to the large-to-small layup method which is often taken in practice as a compromise of practicality and restoration of mechanical properties, especially in the general aviation industry. 33 In this sequence, the first layer of reinforcing fabric covers the repair area, followed by successively smaller layers, and is finished with an extra outer layer (Figure 4(d)). 34 The plain weave repair plies have half the dry areal weight of the facesheet twill-weave plies and are 0.5 mm thinner.…”
Section: Repair Processmentioning
confidence: 99%
“…The patch was fabricated by placing the largest ply as a first taper layup sequence according to the large-to-small layup method which is often taken in practice as a compromise of practicality and restoration of mechanical properties, especially in the general aviation industry. 33 In this sequence, the first layer of reinforcing fabric covers the repair area, followed by successively smaller layers, and is finished with an extra outer layer (Figure 4(d)). 34 The plain weave repair plies have half the dry areal weight of the facesheet twill-weave plies and are 0.5 mm thinner.…”
Section: Repair Processmentioning
confidence: 99%
“…Although attempts are made to transfer the stress to the interior structure, the GFRP composite material is also heavily stressed. Problems arise when dynamic loading changes the direction of the principal stresses, which are no longer directed along the reinforcement fibers [ 12 ]. Therefore, the orientation of the reinforcement fibers is of particular importance both for the realization of the strength conditions of the blades and for the economic aspects of material economy.…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that the linear transversely isotropic model is adequately accepted as the estimation method of the GFRP composite structure response. journal.ump.edu.my/ijame ◄ researchers and naval architects to investigate the mechanical behavior of composite due to specific loading conditions [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%